A inserção na educação de jovens e adultos e a formação da identidade profissional docente: um estudo de caso - Cavalcanti, Israel Sharon Silveira (2016)
This article aims to investigate the professional identity of the teachers of the Education of Young and Adults (EJA) at Ferreira Itajubá Municipal School, in Natal, the capital of Rio Grande do Norte. Through this research it is possible to comprehend the repercussion of teachers´ immersion in the EJA modality, the professional qualification, based on identity concepts (GIDDENS, 2002; HALL, 2011; 2014; CASTELLS, 2008; BAUMAN, 2013) and teaching (TARDIF; LESSARD, 2012; ARROYO, 2000, 2006; PERRENOUD, 1997). All the data was analysed by the methodology of the comprehensive interview. The data was collected by asking semi-open questions to the teachers who worked in the 3rd and 4th levels of this modality in this school. The content analysis (BOGDAN; BIKLEN, 1994; BARDIN, 2011) ranked data in seven topics: formation, which is related to the graduation choice; why to be a teacher, which analyzes the reasons that led to the teaching career; arrival at EJA, which reveals how teachers got into this modality; to be an EJA teacher, which search the meanings of the teachers in the profession; idea about EJA, which is related to how teachers see this modality, EJA dream, related to a modality idealized by the teachers; and the EJA student, which shows teachers and students relationship. The issues were addressed in two analysis categories: teaching admission and EJA insertion. In the end of the study, these categories showed the conflict between personal and professional spheres experienced by the teachers, revealing that EJA insertion has contributed to a social role unveiling as educator and reassert the identity as a teacher.